Formulation of nanoparticles from short chain chitosan as gene delivery system and transfection against T47D cell line - Lina Winarti; Ronny Martien; Sismindari . (Indonesian Journal of Pharmacy, 2011)
Recently numerous prototype DNA-based biopharmaceuticals can be used to  control  disease  progression  by  induction  and  inhibitin  the  overexpression  of genes.  Since  there  are  poor  cellular  uptake  and  rapid  in  vivo  degradation  of DNA-based  therapeutics  therefore  the  use  of  delivery  systems  to  facilitate cellular internalization and preserve their activity is necessary. Cationic polymers commonly used as carriers to delivery gene because of easy to form complexes and  higher  stability  compared  to  that  lipoplexs.  Chitosan,  a  cationic,  are polymer most widely used in gene delivery systems because of the low toxicity, and biocompatible. The aim of this study was to formulate nanoparticles of short chain  chitosan-pEGFP-C1  and  short  chain  chitosan/TPP-pEGFP-C1  by coaservation  complex  method.  Stability  test  of  the  formula  was  performed  by incubating the nanoparticles complex with DNase I and Artificial Intestinal Fluid. Cytotoxicity  and transfection  studies  were  evaluated  against  T47D  cell line.  The diameter  of  Chitosan-pEGFP-C1  and  chitosan/TPP-pEGFP-C1  nanoparticles  were on the range of 56–282.8 nm. The zeta potential wasdetermined to be +14.03 - +16.6  mV.  Stability  studies  showed  that  chitosan-pEGFP-C1  and  chitosan/TPPpEGFP-C1  nanoparticles  were  stable,  undegradable  by  DNase  I  and  artificial intestinal fluid. Cytotoxic Assay of Chitosan-pEGFP-C1 and  chitosan/TPP-pEGFPC1  nanoparticles  (pH  4.0)  showed  that  the  viability  of cell  was  >  90%  for  all formulas.  EGFP-C1  plasmid  gene  delivered  by  chitosan  nanoparticles  can  be expressed  in  T47D  cell  culture.  According  to  these  results  chitosan  and chitosan/TPP  nanoparticles  had  potentially  to  be  used  as  a  non-viral  vector system delivery for gene therapy.Key words:Chitosan, Nanoparticles, Plasmid EGFP-C1, Cell culture T47D